Continuous evolution of clinical phenotype in 578 Japanese patients with Behçet's disease: a retrospective observational study. Issue 1 (December 2016) - Kirino, Yohei; Ideguchi, Haruko; Takeno, Mitsuhiro; Suda, Akiko; Higashitani, Kana; Kunishita, Yosuke; Takase-Minegishi, Kaoru; Tamura, Maasa; Watanabe, Toshiyuki; Asami, Yukiko; Uehara, Takeaki; Yoshimi, Ryusuke; et al.
Abstract Background It has been suggested that the phenotypes of Behçet's disease (BD) in Japan are changing. To ask whether the evolution of BD holds true in recent-onset cases in Japan, we performed a retrospective study. Methods We reviewed the records of 578 patients with BD who met the 1987 revised diagnostic criteria of the Behçet's disease research committee of Japan. The patients were divided into three groups based on the date of disease onset. We compared the demography, clinical features, and treatments among them with or without adjustment for the observation period. Patients having oral ulcers, genital ulcers, regional skin involvement, and uveitis are categorized as having complete-type BD, and the associated factors were determined by univariate and multivariate logistic regression analyses. Results Male patients had a higher propensity for uveitis and central nervous system (CNS) involvement, whereas female patients had higher rates of genital ulcers and arthritis. We found a significant trend in reduction of complete-type, genital ulcer, HLA-B51 carriers, and increment of gastrointestinal BD over time. Multiple regression analysis identified HLA-B51 positivity, earlier date of disease onset, and younger age of onset as independently associated with complete-type BD. Although treatments had been also chronologically changed, the causative relationship between therapeutic agents and phenotypical changes was not determined from the study. Conclusion The present study revealed that phenotypical evolution was characterized by decreased incidence of the complete type and increment of gastrointestinal involvement in Japanese patients with BD during the last 30 years.